Determinants of Factors Causing Unwanted Pregnancy in Adolescents: A Literature Review - Dewa Ayu Dewi Permata Sari; Diah Indriani (Media Gizi Kesmas, 2021)
ABSTRACTBackground: The Phenomenon of unwanted pregnancy among adolescents is still rife in Indonesia. Results of interviews with the head of the National Population and Family Planning Agency (BKKBN), Hasto Wardoyo, explained in 2020 that there are not enough unwanted pregnancies in Indonesia which reach 17.5%.Objectives: Provide an overview of the determinants of unwanted pregnancy in adolescents in Indonesia.Methods: An article search was conducted using Google Scholar and Garuda Portal with the keywords "unwanted pregnancy", "unwanted pregnancy in adolescents aged 12-24 years", "unwanted” pregnancy factor in adolescents". Discussion: The total articles obtained were 157 articles, found 5 articles that met the inclusion criteria, namely articles with research conducted in Indonesia with publication years from 2015 to 2020, in the form of original articles, articles available in full text and free access, as well as factors causing pregnancy in adolescents. Lack of knowledge, permissive attitude of adolescents, easy access to pornographic media and parenting patterns are factors that cause pregnancy in adolescents.Conclusions: Lack of knowledge of adolescents about reproductive health and sexual health is the most dominant factor as a cause of unwanted pregnancy among adolescents, because knowledge can affect the attitudes and behavior. It is necessary to provide guidance and counseling related to knowledge andunderstanding to adolescents and parents regarding adolescent reproductive health.Keywords: Unwanted pregnancy, adolescents, unwanted pregnancy factors in Indonesia